1976
DOI: 10.1530/acta.0.0830114
|View full text |Cite
|
Sign up to set email alerts
|

The Pancreatic Alpha and Beta Cells Responses to 1-Arginine and Insulin-Induced Hypoglycaemia in Hyperthyroidism

Abstract: In order to assess the secretory capacity of the pancreatic alpha and beta cells in patients with hyperthyroidism, the plasma glucagon and insulin responses to 1-arginine and insulin-induced hypoglycaemia in 12 patients were compared with those in 6 normal subjects. The response of beta cell to hypoglycaemia was evaluated by measuring the decrease in plasma C-peptide immunoreactivity (CPR) level. There was a negligible rise in blood glucose and plasma insulin levels in the patients, whereas a significant incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

1977
1977
2001
2001

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…In the present report it has been shown that an elevation of the circulating insulin concentration to levels comparable to those (Shima et al 1976) attained ten minutes after the rapid injection of insulin. 0.1 U per kg body weight.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In the present report it has been shown that an elevation of the circulating insulin concentration to levels comparable to those (Shima et al 1976) attained ten minutes after the rapid injection of insulin. 0.1 U per kg body weight.…”
Section: Discussionsupporting
confidence: 61%
“…have shown suppression of a secretory function of B cells in healthy subjects and patients with hyperthyroidism during insulin-induced hypoglycemia (Shima, Sawazaki, Morishita, Tanaka, Tarui and Nishikawa 1976). Similar findings were obtained in normal subjects by Horowitz, Rubenstein, Reynolds, Molnar and Yanaihara (1975).…”
Section: Introductionsupporting
confidence: 69%
“…However, this alteration was mainly due to a marked elevation in three of nine patients; the remaining six patients showed normal values ( Table 2). In two previous studies (10,11), basal plasma glucagon levels were reported to be normal, although no detailed data regarding individual patients were made available. Recently, it has been demonstrated that in rats rendered hyperthyroid by ip administration of T 4 (500-1500 jug/kg BW) for 9 days, portal venous plasma glucagon was markedly elevated (12).…”
Section: Discussionmentioning
confidence: 99%
“…Insulin sensitivity would have reflected the concentration of insulin receptors on target cells, which is known to be inversely related to the concentration of circulating insulin (Soll et al, 1975a,b). The secretion of insulin in response to nutrients such as glucose (Renauld et al, 1971;Cavagnini et al, 1974;Lenzen et al, 1976;Okajima & Ui, 1978) and arginine (Imura et al, 1976;Shima et al, 1976) was reported to be severely impaired in hyperthyroidism. Though the insulinaemic action of fl-adrenergic agents was conversely enhanced by hyperthyroidism (Okajima & Ui, 1978), nutritional stimuli might be more intense and more frequent than sympathetic stimuli to cause a normal daily rhythm of insulin secretion.…”
Section: Sensitivity Of Hyperthyroid Rats To Glycaemic Action Of Insulinmentioning
confidence: 99%